G. Gall (επιμ.), Union Revitalization in Advanced Economies: Assessing the Contribution of Union Organizing. - Μπιθυμήτρης, Γιώργος (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2015)
[Δεν διατίθεται περίληψη / no abstract available]